Prestressed concrete - Magnel, Gustave (Concrete Publications, 1948)
This title includes a history of prestressed concrete, discusses different methods of inducing a compressive stress in concrete, and provides a systematic solution for the design of prestressed concrete members in both statically-determinate structures and continuous beams with equal spans; it details laboratory tests into aspects of prestressed concrete, and concludes with a section on its application principally in Belgium.